Financial Distress and Happiness of Employees in Times of Economic Crisis - Efstratia Arampatzi; Martijn J. Burger; Ruut Veenhoven (Tinbergen Institute, 2014)
Using data for 28 European countries for the 2008-2012 period, we examine whether employed individuals are affected by the economic crisis. We provide robust evidence that unfavourable macroeconomic conditions are negatively associated with the life satisfaction of employees. In addition, we find that higher levels of regional unemployment and inflation are predominantly associated with lower levels of life satisfaction for employees who are in a bad financial situation or who expect that their future financial situation will be worse. By contrast, employed people who do well financially and who have good prospects are not affected by the crisis.
Keywords: I00; D60; 330; life satisfaction; financial distress; economic crisis; Europe